THE USE OF DIGITAL STORY IN TEACHING WRITING NARRATIVE TEXT - Lilies Youlia Friatin; Umi Jauharoh (Universitas Galuh, 2017)
This study deals with investigating of the use of digital story in teaching writing narrative text. Furthermore, in conducting this study the researchers used qualitative research in which case study was employed to collect the data from participants in this research that was English teacher who used digital story in teaching writing narrative text. This study used purposive as a sampling technique. There were two instruments used by the researchers in conducting the study such as observation and interview. The results showed that teacher’s ways in teaching writing narrative text by using digital story were implemented as follows. Firstly, the teacher explained the material concerning the theme on that day, and then the teacher presented the example of narrative text by using digital story, after that the teacher instructed the students to work in group in order to make thenarrative text script and search images, audio, and background from internet that relevant with their topic of the story. The next activity, the teacherinstructed the students to sit with their group to make a digital story with the script and images, audio, and background that was students search. Finally, teacher instructed the students to present their digital story in front of the class and then asked the other group to comment the performance of group who perform in front of the class. In addition, digital story can be used to motivate students writing, improve presentation skill or academic performance in front of the class, and improve their understanding of teacher’s material. Besides, digital story let students own their creative work, taking the narrative process to them. The use of digital story in teaching writing narrative text also makes the students felt fun and not bored in the classroom. Based on the results of this study, the writer concludes that digital story is one of appropriate teaching media that can be used by the teachers. Keywords:Teaching writing, teaching media, digital story, digital storytelling, narrative text.